2018
DOI: 10.1080/1028415x.2018.1486940
|View full text |Cite|
|
Sign up to set email alerts
|

Nutritional status is associated with the degree of cognitive impairment and depressive symptoms in a Greek elderly population

Abstract: A high prevalence of malnutrition was recorded in this elderly population sample, which was directly associated with cognitive impairment and depression. Diagnostic tools such as MNA, MMSE, and GDS are strongly recommended to be applied as a routine clinical practice in the elderly to timely and effectively address these health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 64 publications
6
58
2
3
Order By: Relevance
“…As far as cognitive status is concerned, in the present study, 63.26% of the participants had normal cognitive status, 36.74% of them had cognitive impairment according to the MMSE score. Recent studies have shown that the prevalence of cognitive impairment was 32.9%-34.4% [23,24]. Our results are comparable.…”
Section: Discussionsupporting
confidence: 82%
“…As far as cognitive status is concerned, in the present study, 63.26% of the participants had normal cognitive status, 36.74% of them had cognitive impairment according to the MMSE score. Recent studies have shown that the prevalence of cognitive impairment was 32.9%-34.4% [23,24]. Our results are comparable.…”
Section: Discussionsupporting
confidence: 82%
“…Regarding monthly income, in Portugal, some individuals did not have a regular income, and no participant had an income above the minimum wage, a situation opposite to that in Brazil, where participants had a higher level of income, despite their worse nutritional and depressive assessments. It is known that the quality of food is usually associated with how much income an individual or family has, and consequently, this aspect is inversely related to the risk of malnutrition/malnutrition (12,13) . Governmental measures for the selection and inclusion of these groups in income transfer programs, especially the Social Insertion Income (SII) in Portugal, can minimize the risk of malnutrition/malnutrition among elderly people, which aims to alleviate poverty, improve living conditions and health and encourage healthy habits (34) .…”
Section: Discussionmentioning
confidence: 99%
“…Depression is believed to be a component strongly associated with cognitive decline and malnutrition in older individuals (12,13) . With these disorders, neurodegenerative processes in speci c brain regions and of genetic factors and in ammatory processes consequently alter nutritional status and cause dementia (cerebral atrophy), which can affect regions of the brain involved in regulating appetite and eating behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Encontramos que la cuarta parte de los sujetos ancianos presentaban un estado de malnutrición (bajo peso), porcentaje mucho mayor a lo reportado por Dosil et al, quienes evaluaron, según el mismo estándar de medición, a ancianos mayores de 65 años y encontraron una frecuencia de bajo peso del de 10,8% [10] . Adicionalmente, un estudio realizado por Mantzorou et al, utilizando la escala Mini Nutritional Assessment -que incluye la medición de IMC-, encontró que el 11,3% de las personas mayores eran desnutridas y el 35% estaba en riesgo de desnutrición [26] . Recientemente, Avendaño estimó que el 18,6% de un grupo de adultos mayores padecía de desnutrición [9] , mientras que Malara et al encontraron que el 30% de un grupo de pacientes ancianos tenía desnutrición [11] .…”
Section: Discussionunclassified
“…Un estudio realizado entre 174 internos de un hogar de ancianos en Calabria-Italia por Malara et al apunta también hacia la misma conclusión, puesto que encontraron una fuerte correlación entre el deterioro cognitivo evaluado por MMSE y el empeoramiento del estado nutricional [11] . Otros estudios como el de Avendaño [9] en España y Mantzorou et al [26] en Grecia también muestran que el estado de desnutrición se asoció directamente con el deterioro cognitivo evaluado por MMSE.…”
Section: Discussionunclassified